2022
DOI: 10.4049/jimmunol.2100708
|View full text |Cite
|
Sign up to set email alerts
|

Altered Offspring Immunity in Maternal Parasitic Infections

Abstract: Maternal infection during pregnancy is known to alter the development and function of offspring’s immune system, leading to inappropriate immune responses to common childhood infections and immunizations. Although this is an expanding field, maternal parasitic infections remain understudied. Millions of women of reproductive age are currently at risk for parasitic infection, whereas many pregnant, chronically infected women are excluded from mass drug administration due partially to a lack of resources, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 104 publications
(76 reference statements)
0
6
0
14
Order By: Relevance
“…Although it is well established that maternal infections, specifically parasitic ones, can shape offspring immunity (10)(11)(12)(13)(60)(61)(62)(63), it is still unknown what factors influence offspring B cell development. Many current studies focus on TORCH (Toxoplasmosis, other (syphilis, varicellazoster, parvovirus B19), Rubella, Cytomegalovirus, and Herpes) infections (64), or common congenital infections, with little effort on how non-congenital maternal infections affect offspring immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well established that maternal infections, specifically parasitic ones, can shape offspring immunity (10)(11)(12)(13)(60)(61)(62)(63), it is still unknown what factors influence offspring B cell development. Many current studies focus on TORCH (Toxoplasmosis, other (syphilis, varicellazoster, parvovirus B19), Rubella, Cytomegalovirus, and Herpes) infections (64), or common congenital infections, with little effort on how non-congenital maternal infections affect offspring immunity.…”
Section: Discussionmentioning
confidence: 99%
“…While an inappropriate excess of Th2 cytokines can prolong virus clearance (7), these cytokines can also decrease chronic, autoimmune-induced inflammation (8). Maternal parasitic infections can mirror these disease outcomes in offspring, such as decreased responsiveness to antigens and protection from the development of some allergies and other chronic diseases (9)(10)(11)(12). Yet, a decrease in Th2 cytokines is observed in mouse models of maternal schistosomiasis, due to epigenetic regulation of the transcription of these cytokines (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, although helminths cannot pass the placental barrier, children born to mothers infected with either Brugia malayi or soil‐transmitted helminths are more susceptible to future helminthiasis due to their immune systems being primed for infection in utero 59,60 . In general, immune hyporesponsiveness leads to an increased susceptibility to other kinds of infections, such as tuberculosis and HIV 8,9,58 . Furthermore, helminth infection during pregnancy has been linked to a decreased efficacy of childhood vaccinations later in life, which correlates with the decreased response to common vaccines observed in certain communities with a high prevalence of parasitic infections 9,61–63 .…”
Section: Immune System Development and Responsementioning
confidence: 99%
“…In general, immune hyporesponsiveness leads to an increased susceptibility to other kinds of infections, such as tuberculosis and HIV 8,9,58 . Furthermore, helminth infection during pregnancy has been linked to a decreased efficacy of childhood vaccinations later in life, which correlates with the decreased response to common vaccines observed in certain communities with a high prevalence of parasitic infections 9,61–63 . These studies have indicated that either pre‐ or post‐natal exposure to helminths can have a long‐lasting effect on the development and responsiveness of the child's immune system to environmental stimuli.…”
Section: Immune System Development and Responsementioning
confidence: 99%
See 1 more Smart Citation